Investigating defensive organisations and psychic retreats in anorexia. - Kadish, Yael Adira (My University, 2013)
This psychoanalytically informed research project combines three theoretical trajectories together with illustrative clinical material to present an exploration of anorexia through a particular conceptual lens. The three theoretical areas are synthesised in an original way through the ideas and arguments presented in the thesis. The theory included: contemporary understandings of eating disorders; contemporary Kleinian literature on pathological organisations and psychic retreats (Steiner, 1982; 1987; 1992; 1993; 2011); and literature on autistic-like (autistoid) defences in non-autistic adults (S. Klein, 1980; Tustin, 1972; 1973; 1978; 1981; 1986; 1991). The research aimed to interrogate and explicate the relationship between pathological organisations of personality structure in anorexia, using case studies and vignettes to illustrate and elaborate the arguments. There was also some consideration of other types of eating disorder, similarly conceptualised. Case material from clinical work as a psychoanalytically informed psychotherapist was used as data in all but one case, in the latter instance interview material being used. The body of the thesis was structured in the form of four journal articles.
Keywords: Anorexia--Psychological aspects.; Anorexia--Treatment.